2006
DOI: 10.1158/1078-0432.ccr-06-0274
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cripto-1 as a Novel Serologic Marker for Breast and Colon Cancer

Abstract: Purpose: Human Cripto-1 (CR-1), a cell membrane glycosylphosphatidylinositol-anchored glycoprotein that can also be cleaved from the membrane, is expressed at high levels in several different types of human tumors.We evaluated whether CR-1is present in the plasma of patients with breast and colon cancer, and if it can represent a new biomarker for these malignancies. Experimental Design: We determined CR-1 plasma levels using a sandwich-type ELISA in 21 healthy volunteers, 54 patients with breast cancer, 33 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 36 publications
6
80
0
1
Order By: Relevance
“…This study further demonstrated that Cripto, a prominent mediator of the Nodal signaling pathway in embryological systems, also is restricted to multipotent cancer and stem cell fates. Previous studies, from other laboratories, determined that like Nodal, Cripto is expressed in cancer, specifically testicular, colon and breast cancer cells, but is rarely detected in normal adult tissues (22)(23)(24). Furthermore, Cripto is a stem cell marker for pluripotent hESCs and has been associated with dedifferentiation, vascularization and invasion in breast carcinoma cells (23,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…This study further demonstrated that Cripto, a prominent mediator of the Nodal signaling pathway in embryological systems, also is restricted to multipotent cancer and stem cell fates. Previous studies, from other laboratories, determined that like Nodal, Cripto is expressed in cancer, specifically testicular, colon and breast cancer cells, but is rarely detected in normal adult tissues (22)(23)(24). Furthermore, Cripto is a stem cell marker for pluripotent hESCs and has been associated with dedifferentiation, vascularization and invasion in breast carcinoma cells (23,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…5A). In addition, significantly higher levels of Cripto-1 can be detected by immunoassay in the plasma of breast cancer patients as compared to Cripto-1 levels detected in healthy controls suggesting that Cripto-1 might be useful in the early diagnosis of this disease [94] (Fig. 5A).…”
Section: Diagnostic and Therapeutic Applicationmentioning
confidence: 98%
“…19 Additionally, both forms of cancer have an increased expression of FAK and CR-1. 20,21 In addition to expressing similar biomarkers, morphologically both MCF-7 (Ref. 22) and HCT 116 (Ref.…”
Section: Introductionmentioning
confidence: 99%